2004
DOI: 10.1086/381043
|View full text |Cite
|
Sign up to set email alerts
|

Priority versus Brute Force: When Should Males Begin Guarding Resources?

Abstract: $15.00. All rights reserved.can also be nonlinear if takeovers are moderately common; if this is the case, then males of intermediate size guard the longest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 44 publications
0
35
0
Order By: Relevance
“…Second, swordtails live in dynamic groupings in which females move between the home ranges of several males (Franck et al 1998). A male that is exclusively guarding a resource that females can utilise is more likely to gain access to females when they arrive and will save energy that would have been used in searching for females (Brown 1964;Archer 1988;Huntingford and Turner 1987;Grant 1993;Härdling et al 2004). In the present study it appears that male swordtails defend a food resource and probably take advantage of female presence at that resource.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, swordtails live in dynamic groupings in which females move between the home ranges of several males (Franck et al 1998). A male that is exclusively guarding a resource that females can utilise is more likely to gain access to females when they arrive and will save energy that would have been used in searching for females (Brown 1964;Archer 1988;Huntingford and Turner 1987;Grant 1993;Härdling et al 2004). In the present study it appears that male swordtails defend a food resource and probably take advantage of female presence at that resource.…”
Section: Discussionmentioning
confidence: 99%
“…Both male size (Beaugrand et al 1991;Benson and Basolo 2006) and sword length (Benson and Basolo 2006) influence the outcome of competitive interactions. Moreover many studies of resource defence, in fish and other taxa, cite male size as a major influencing factor (Beaugrand et al 1991;Morris et al 1992;Beaugrand and Goulet 2000;Härdling et al 2004;Benson and Basolo 2006;Ward et al 2006). Larger, stronger males are usually able to outcompete smaller males (Härdling et al 2004;Ward et al 2006) and so can persevere in individual contests and, if the norm for that species, achieve dominance (Ward et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Mate guarding is most typically described in a variety of animals as a behaviour in which males closely follow their mates to prevent cuckoldry during a female's fertile period (Gowaty 1996), and its expression in the breeding season is mediated by T (Moore 1984). However, females do not have to be fertile for mate guarding to be selectively advantageous (Härdling et al 2004). Even in the nonbreeding season, mate guarding can function to increase a male's assurance of paternity (Artiss & Martin 1995;Guillemain et al 2003).…”
mentioning
confidence: 99%
“…Their results also pointed to a role of interference competition among males in promoting patterns of size-assortative mating in G. pulex (Bollache & Cézilly 2004). In addition, if takeovers are rare, Hardling et al (2004) showed that the best option for mate-searching males must be to choose the best single female available, which is likely to be a large female (Elwood et al 1987).…”
Section: Discussionmentioning
confidence: 99%